Enhancing palliative care for oncology patients: The effect of educational intervention on nurses competency and Attitude - Hussein, Nada Salim; Mohamed, Magda Ahmed; Ahmed, Rasha Ali (South Eastern European Journal of Public Health, 2024)
Background: Cancer is the second leading cause of death so the need for palliative care has increased to enhance patient’s quality of life and alleviate suffering. Nurses level of competency and attitude about palliative care are important factors affecting quality of care applied for patients. Aim: Assess and evaluate the nurses' competency and attitude regarding palliative care of cancers patients. Design: Pre -experimental (one group pre/posttest) design. Sample: A convenient sample of all available nurses (120). Setting: The study was carried out in Aswan Oncology Institute. Tools: Tool I: A structured interview questionnaire for nurses to assess nurse’s knowledge regarding palliative care, tool II: Nurses' observational checklist to assess nurses’ practices related to palliative care and tool III: Nurses' attitude toward palliative care. Results: The total score of nurses' knowledges had improved from 51.8% to 75.9% pre/post the intervention, concerning nurses’ total practices ,39.3% of the studied nurses had competent level of practice pre the intervention which improved to (82.1%) post intervention. Hundred percent of the studied nurses had negative attitude pre-palliative care intervention, while post 43.8% had negative attitude. Conclusion: Palliative care training package had significant improvement in nurses' attitude and competencies. Recommendations: Continuous in-service training program should be conducted periodically in order to update nurses' knowledge and improve their competencies levels regarding palliative cares.